Second general report on the activities of the communities 1968 - Eurpoean Economic Community; European Atomic Energy Community (Luxemburg : Eurpoean Coal and Steel Company, 1969)
Alone of all the large European organizations, the Communities have succeeded in building up and administering common policies, and this they owe essentially to their institutional machinery
osc 25/01/2019
Ref
Keywords: Economic integration